TIM3 expression by leukemic and non‐leukemic myeloblasts1. Issue 3 (29th March 2013) - Roth, Christine G.; Garner, Kelly; Eyck, Stephen Ten; Boyiadzis, Michael; Kane, Lawrence P.; Craig, Fiona E.
Abstract: Background: T‐cell immunoglobulin mucin‐3 (TIM3) has recently been described as an acute myeloid leukemia (AML) stem cell antigen expressed on leukemic myeloblasts, but not on normal hematopoietic stem cells. TIM3 is also expressed by monocytes, natural killer cells, and several T cell subsets; however, normal myeloblasts have not been well‐characterized or compared to AML. A specific flow cytometric marker capable of separating leukemic myeloblasts from non‐neoplastic myeloblasts would be diagnostically useful, especially in the post‐chemotherapy setting. Methods: TIM3 myeloblast expression was assessed in 69 bone marrow and/or peripheral blood specimens, including 27 AML and 42 non‐neoplastic cases (20 with a recent history of chemotherapy). TIM3 median fluorescence intensity (MFI) was evaluated within myeloblast, monocyte, T cell, and natural killer cell populations. Results: The median percentage of myeloblasts positive for TIM3 was lower in non‐neoplastic specimens without a history of recent chemotherapy (50.3%) as compared to AML (71.4%), but not significantly different as compared to non‐leukemic myeloblasts in the post‐chemotherapy setting (72.4%). Mean myeloblast TIM3 MFI was higher in AML myeloblasts and non‐leukemic myeloblasts in the post‐chemotherapy setting as compared to non‐neoplastic myeloblasts in cases lacking a history of chemotherapy. Mean monocyte, natural killer cell, and T‐cell TIM3 MFI remained relatively constant in varied clinical settings. Conclusions: We confirm that leukemic myeloblasts overexpress TIM3 as compared to non‐neoplastic controls; however, high levels of expression may also be seen among non‐leukemic myeloblasts in the post‐chemotherapy setting. This overlap limits the diagnostic utility of TIM3 as a specific marker of neoplasia. © 2013 International Clinical Cytometry Society